Characteristics and outcomes among patients with community‐acquired respiratory virus infections during the first year after lung transplantation. Issue 1 (20th November 2020) - Mahan, Luke D.; Kanade, Rohan; Mohanka, Manish R.; Bollineni, Srinivas; Joerns, John; Kaza, Vaidehi; Torres, Fernando; La Hoz, Ricardo M.; Banga, Amit
Abstract: Background: The current study describes the spectrum of community‐acquired respiratory infections (CARV) during the first year after lung transplantation (LT). Additionally, we elucidate variables associated with CARV, management strategies utilized, and impact on early and late outcomes. Methods: This was a retrospective study among patients transplanted between 2012 and 2015 ( n  = 255, mean age 55.6 ± 13.5 years, M: F 152:103). The diagnosis of CARV was based on the multiplex PCR on nasopharyngeal swab samples. Baseline characteristics, post‐transplant variables, and outcomes were compared among patients with and without CARV. Results: Eighty CARV infections developed among a quarter of the study group ( n  = 62, 24.3%). Rhinovirus/enterovirus was the most commonly isolated CARV ( n  = 24) followed by coronavirus ( n  = 17) and RSV ( n  = 9). A significant proportion of episodes (43.8%) required hospitalization. The use of nasal corticosteroids and left single LT was independently associated with an increased risk of CARV. CARV infections did not impact the lung functions during the first year or the CLAD‐free survival at 3 years. Conclusions: There is a significant burden of CARV infections during the first year after LT. The use of nasal corticosteroids may increase the risk of CARV infection. CARV infections did not impact outcomes.